STUDY ON RHEOLOGICAL BEHAVIOR AND CONSTITUTIVE MODEL OF TA17 TITANIUM ALLOY AT HIGH STRAIN RATE - JIA HaiShen; XIA ShiYu; ZHANG JiLin; LUO WenCui; SHEN JianCheng; CHEN YanXiang; XU ChuangWen (Jixie qiangdu)
The quasi-static(Strain rate of 0.001 s-1～0.01 s-1) and dynamic(Strain rate of 1000 s-1 ～ 5 000 s-1) compression tests of TA17 titanium alloy were conducted on at 25℃. The strain hardening characteristics and the mechanism of strain rate on its rheological behavior were studied, and the rheological characteristics under high strain rates were quantitatively studied by means of strain hardening index（n） and strain rate sensitivity index（m）. Based on the dynamic rheological characteristics of TA17 titanium alloy and considering the influence of the coupling between strain and strain rate on its flow stress, a new J-C constitutive model is constructed. based on the obtained experimental data, the model parameters are identified, the predicted values of the model are compared with the experimental data, and the two parameters of correlation coefficient（R） and average absolute relative error are introduced to evaluate the prediction accuracy of the constructed constitutive model.The results show that TA17 titanium alloy exhibits obvious strain hardening, strain rate strengthening and strain rate plasticizing effects, and its rheological behavior is dominated by strain, strain rate and the coupling between them. The strain hardening index decreases with the increase of strain and strain rate, while the strain rate sensitivity index increases with the increase of strain rate, and decreases with the increase of strain. The correlation coefficient（R） of constructed constitutive model is 0.997 7 and the average absolute relative error is 0.27%.